We can solve this problem through the use of Pythagorean's Theorem. It states that that the square of the first leg plus the square of second leg is equal to the square of the hypotenuse: [tex]a^2+b^2=c^2[/tex]
Let's input the information we're given from the diagram. → We know that the first leg is equal to 24 → We also know that the hypotenuse is equal to 26
The equation with the imputed information: [tex]24^2+b^2=26^2[/tex]
Simplify the equation: [tex]576+b^2=676[/tex]
Add -576 to both sides of the equation: [tex](576+b^2)(-576)=(676)(-576)[/tex]
[tex]b^2=100[/tex]
Find the Square Root of both sides: [tex] \sqrt{b^2}= \sqrt{100} [/tex]